2012
DOI: 10.1590/s0085-56262012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citrus floral extracts on the foraging behavior of the stingless bee Scaptotrigona pectoralis (Dalla Torre)

Abstract: Effect of Citrus floral extracts on the foraging behavior of the stingless bee Scaptotrigona pectoralis (Dalla Torre). Stingless bees have an important role as pollinators of many wild and cultivated plant species in tropical regions. Little is known, however, about the interaction between floral fragrances and the foraging behavior of meliponine species. Thus we investigated the chemical composition of the extracts of citric (lemon and orange) flowers and their effects on the foraging behavior of the stingles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…Towards the end of the morning, a decrease in number of landing bees suggests that flowers become less attractive due to senescence close to midday or after previous floral visits, as reported earlier for several plant species (van Doorn, 1997). Trigona landed almost exclusively on the labellum and exhibited a probing behavior indicative of foraging (Armbruster, 1984;Slaa et al, 1998;Nieh, 2004;Lichtenberg et al, 2010;McCabe & Farina, 2010;Grajales-Conesa et al, 2012). Euglossa and Eulaema were observed more frequently on the tepals, repeatedly brushing with their foretarsi, then hovering around while transferring compounds to their hind tibia, indicating fragrance collection (Dressler, 1968;Whitten et al, 1989;Eltz et al, 2003).…”
Section: Discussionmentioning
confidence: 59%
“…Towards the end of the morning, a decrease in number of landing bees suggests that flowers become less attractive due to senescence close to midday or after previous floral visits, as reported earlier for several plant species (van Doorn, 1997). Trigona landed almost exclusively on the labellum and exhibited a probing behavior indicative of foraging (Armbruster, 1984;Slaa et al, 1998;Nieh, 2004;Lichtenberg et al, 2010;McCabe & Farina, 2010;Grajales-Conesa et al, 2012). Euglossa and Eulaema were observed more frequently on the tepals, repeatedly brushing with their foretarsi, then hovering around while transferring compounds to their hind tibia, indicating fragrance collection (Dressler, 1968;Whitten et al, 1989;Eltz et al, 2003).…”
Section: Discussionmentioning
confidence: 59%
“…This sesquiterpenoid is commonly found in propolis (a resinous beehive product), citrus fruits and various plant essential oils, such as Tetradenia riparia [ 223 ] and Citrus sp. [ 224 ]. In study performed by Qamar and Sultana [ 225 ], FAR showed protective efficacy against massive lung inflammation, oxidative stress and injuries induced by cigarette smoke toxicants.…”
Section: Resultsmentioning
confidence: 99%
“…Flowers of Citrus depressa also emitted linalool and myrcene, as well as ocimene (Loper, 1972). Linalool is a major component of the floral extract of Citrus sinensis, which also contains myrcene and ocimene (Grajales-Conesa et al, 2012). The floral extract of Citrus limon includes myrcene, trans-ocimene, caryophyllene, a-farnesene, and p-cubebene (Grajales-Conesa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%